Crystal structure of the catalytic D2 domain of the AAA+ ATPase p97 reveals a putative helical split-washer-type mechanism for substrate unfolding - Stach,L; Morgan,RM; Makhlouf,L; Douangamath,A; von,Delft F; Zhang,X; Freemont,PS (FEBS Letters, 2020)
Several pathologies have been associated with the AAA+ ATPase p97, an enzyme essential to protein homeostasis. Heterozygous polymorphisms in p97 have been shown to cause neurological disease, while elevated proteotoxic stress in tumours has made p97 an attractive cancer chemotherapy target. The cellular processes reliant on p97 are well described. Highresolution structural models of its catalytic D2 domain, however, have proved elusive, as has the mechanism by which p97 converts the energy from ATP hydrolysis into mechanical force to unfold protein substrates. Here, we describe the highresolution structure of the p97 D2 ATPase domain. This crystal system constitutes a valuable tool for p97 inhibitor development and identifies a potentially druggable pocket in the D2 domain. In addition, its P61 symmetry suggests a mechanism for substrate unfolding by p97.